Women and Terrorism - Neuburger, Luisella de Cataldo. author. aut Link
VIII, 178 p.
Keywords: Women and Terrorism analyses a new phenomenon of international concern: the participation of women in subversive terrorist movements. The book deals with four main issues: 1) women's participation in violent terrorist movements to discover the key to the psychological and sociological interpretation of their involvement in a life experience they are not traditionally associated with; 2) the different responses to 'penitentism' between men and women; 3) the psychological and social interpretation of women's support of armed struggle and an inquiry - through the personal experience of the women terrorists interviewed - into the reasons for women's greater resistance to repentance; 4) the use of the leads this inquiry has furnished for prognostic purposes and to predict and create conditions that facilitate repentance.